Stability analysis of a virus infection model with humoral immunity response and two time delays. (19th February 2016) - Miao, Hui; Teng, Zhidong; Kang, Chengjun; Muhammadhaji, Ahmadjan
Abstract : In this paper, we investigate the dynamical properties for a model of delay differential equations, which describes a virus‐immune interaction in vivo . By analyzing corresponding characteristic equations, the local stability of the equilibria for infection‐free, antibody‐free, and antibody response and the existence of Hopf bifurcation with antibody response delay as a bifurcation parameter at the antibody‐activated infection equilibrium are established, respectively. Global stability of the equilibria for infection‐free, antibody‐free, and antibody response, respectively, also are established by applying the Lyapunov functionals method. The numerical simulations are performed in order to illustrate the dynamical behavior of the model. Copyright © 2016 John Wiley & Sons, Ltd.